RECONSTRUCTION OF BASIC CONCEPTS OF THE IMPLEMENTATION OF PROGRESSIVE ISLAM IN STUDENT ACTIVITIES - Teguh Luhuringbudi; Emah Rahmaniah; Fitri Liza; Dewi Nita Utami (Jurnal Pemikiran Islam, 2021)
This paper is not only aimed at disagreements with the views of Dina Rafidiyah and Fasho Tio Anugrah and their efforts to develop their thoughts, but also presents a basic concept formula for the application of progressive Islam that is simple and easy to apply in student activities at Muhammadiyah Higher Education. Researchers used a media approach through a globalization perspective introduced by Gill Branston and Roy Stafford in analyzing student activity at Muhammadiyah Higher Education as the object of this study. The conclusion of this study is the provision of material for students' understanding of the concept of progressive Islam and the application of its values that emphasize creativity and innovation through the basis of the Quran in the behavior and cultural life of the campus. This paper also produces derivative findings that come from these conclusions. The first finding is the need for material for students' understanding of the concept of progressive Islam that emphasizes creativity and innovation through the Quranic basis in behavior such as aspect of academic maturity in social media; and aspect of social action in everyday life. The second finding is the application of Progressive Islamic values in the cultural life of the campus through the aspect of guarding and ending learning by studying thematic Quranic verses; and aspect of career assurance and business experience-skills provision.